PENGARUH BLANCHING DAN UKURAN PARTIKEL (MESH) TERHADAP KADAR GLUKOMANAN, KALSIUM OKSALAT DAN SERAT MAKAN TEPUNG UMBI PORANG (Amorphophallus onchophyllus) - Sri Budi Wahjuningsih; Bambang Kunarto (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2011)
This study aimed to determine the combination of blanching and particle size (mesh) to content of glucomannan, calcium oxalate and fiber on porang flour. Experimental design used was Randomized Complete Design (CRD) of two factors, namely blanching and particle size. Blanching factor consisted two treatments of blanching for 10 minuts (B1) and non-blanching (B2). While particle size factor consisted of three treatments, namely 60 mesh (N60), 80 mesh (N80) and 100 mesh (N100). Data obtained were analyzed with a variety of scales followed by DNMRT at 5% confidence level. Based on the research can be concluded that the larger particles (small mesh) showed increased levels of glucomannan but calcium oxalate on the downside. Combination blanching treatment and particle size of the large (small mesh) showed dietary fiber content increased